2015
DOI: 10.1039/c5ta03465e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and facet-dependent enhanced photocatalytic activity of Bi2SiO5/AgI nanoplate photocatalysts

Abstract: Novel Z-scheme Bi2SiO5/AgI nanoplate photocatalysts with the exposure of {100} facets on the surfaces of Bi2SiO5 nanoplates were synthesized via an in situ precipitation method. Acid red G aqueous solution and gaseous formaldehyde were chosen as model organic pollutants to evaluate the photocatalytic activities of the as-prepared catalysts. Under visible light irradiation (>420 nm), the Bi2SiO5/AgI nanoplates exhibited enhanced photocatalytic activities as compared to the pure Bi2SiO5 or AgI. X-ray photoelectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 134 publications
(47 citation statements)
references
References 44 publications
(60 reference statements)
0
47
0
Order By: Relevance
“…Besides providing these organic matter references, some representative parameters for photocatalysis evaluation have also been summarized and analyzed, such as the apparent rate constant (k app ) and total organic carbon (TOC). [240] benzene Ag/AgCl/TiO 2 /PM [289] acridine orange (AO) Ag@AgX (X = Cl, Br) [308] acid red G aqueous solution Bi 2 SiO 5 /AgI [268] The real-time concentration changes of organic pollutants during photocatalytic degradation are detected through their UV-visible absorbance. According to Lambert-Beer law, actual concentration changes of colored dye molecules (C/C 0 ) are directly proportional to their corresponding normalized UVvis absorption values (A/A 0 ).…”
Section: Performance Evaluation Modes Of Silver Halide In Organic Degmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides providing these organic matter references, some representative parameters for photocatalysis evaluation have also been summarized and analyzed, such as the apparent rate constant (k app ) and total organic carbon (TOC). [240] benzene Ag/AgCl/TiO 2 /PM [289] acridine orange (AO) Ag@AgX (X = Cl, Br) [308] acid red G aqueous solution Bi 2 SiO 5 /AgI [268] The real-time concentration changes of organic pollutants during photocatalytic degradation are detected through their UV-visible absorbance. According to Lambert-Beer law, actual concentration changes of colored dye molecules (C/C 0 ) are directly proportional to their corresponding normalized UVvis absorption values (A/A 0 ).…”
Section: Performance Evaluation Modes Of Silver Halide In Organic Degmentioning
confidence: 99%
“…Heterogeneous system constituted by photoactive semiconductors is regarded as an effective method to facilitate the photoexcited electron-hole separation with enhanced photocatalytic activity [254][255][256][257][258][259][260][261][262][263][264][265][266][267][268][269]. Various metallic semiconductor (such as TiO 2 , ZnO, BiVO 4 ) and metal-free nitrogen-doped graphene semiconductors have been considered as preferred substances to composite with AgX, shown as Table 2.…”
Section: Other Photoactive Semiconductormentioning
confidence: 99%
“…[46,47] The photocatalytic activity of the photocatalyst is related to its structure. [48][49][50][51][52][53][54] Also, the higher photocatalytic activity of K 6 Ta 10.8 O 30 against ARG may be in connection with the TaO 6 octahedrons in the crystal structures and K + in pentagonal tunnels. The highly distorted surface TaO 6 octahedral sites like NbO 6 might facilitate the movement of photogenerated electron-hole pairs, inhibit the recombination of elec-tron-hole pairs and finally increase the catalytic activity of the K 6 Ta 10.8 O 30 catalyst for ARG decomposition.…”
Section: Photocatalytic Degradation Mechanismmentioning
confidence: 99%
“…[18][19] Bismuth oxyhalides were implemented in dyes photodegradation like Rhodamine B, [16] methyl orange, [17] BF dye, [15] orangeII, ARG, and Azure B. [18][19][20] BiOXs have also been applied in organic removal, disinfection and heavy metal reduction from water such as Chromium (VI). [13][14][21][22][23] The studies have demonstrated that they have high performance under visible light.…”
Section: Introductionmentioning
confidence: 99%